Development of fluoride-containing glass–ceramics using eggshells waste as calcium source - Zhi, Wei Loh; Wei, Mun Cheong; Mohd Zaid, Mohd Hafiz; Kechik, Mohd Mustafa Awang; Yap, Wing Fen; Mayzan, Mohd Zul Hilmi; Yaakob, Yazid; Shahira Liza (Springer Nature, 2022)
This paper reports on developing low-cost fluoride-containing glass–ceramics derived from eggshells waste as a source of calcium via the conventional melt-quenching method. The physical, structural, and mechanical properties of the samples before and after sintering is highlighted in this study. XRD and FTIR analysis confirmed the presence of fluorapatite, wollastonite, and cuspidine phases. It is worth noting that adding fluoride to the glass system would lead to the improvement of the mechanical properties of the final product. Among all, the sample sintered at 700 °C achieved the highest density and mechanical properties. It obtained a density value of 2.626 g/cm3, a microhardness result of 6.72 GPa, and fracture toughness of 3.55 MPa·m1/2. These results are better than commercial 45S5 bioglass (0.148 GPa–0.375 GPa) and comparable to the properties of human enamel (2.00 GPa–6.00 GPa). These findings would be believed to contribute to a low-cost waste-derived fluoride-containing glass–ceramics system in the dental application.